Meraih Makna Al-Quran - Achmad Lutfi (MAGHZA, 2019)
The belief of Muslims in the religion they profess is that religion can provide guidance and solutions towards the principal problems faced by humankind throughout the ages. As a consequence, Muslims should be able to prove and elevate Islamic values ​​in the realities of life. In Islamic teaching, the Qur'an becomes the most important manifestation. Al-Qur’an becomes the main source of Islamic teaching which has brought out many Islamic disciplines, as well as being a reference for determining and even justifying the details of the teaching. The problem of understanding and getting the meaning of the concepts recorded in the Qur'an occupies a very significant position in the discourse of Islamic thought today. Farid Esack as one of the figures who have an interest in exploring the meaning of the Qur'an prefers to use hermeneutics as one of the tools in interpreting the Qur'an. With hermeneutics, Esack believes that the meaning of the a-Qur'an can be achieved to make it always fit beyond time and space.